Étude de l'efficacité d'un protocole de remédiation en lecture par des enseignants de cycle 3 - Sophie Briquet-Duhazé (Université de Provence, 2012)
The aim of our research is to implement a predictor of learning to read, phonological awareness, as remediation of difficulties of students aged 8, 9 and 10. Step 0 is used to test the effectiveness of this training that wants long among pupils and for older (unlike the corpus described in international research on phonological awareness). Step 1, currently, the same objective with another sample of students decomposed into control and experimental groups. The second predictor, knowledge of letter names is added, based on the observation of its partial mastery in Grade 9, 10 and 11 years.